2017
DOI: 10.1112/s0010437x17007254
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Serre weights for two-dimensional Galois representations

Abstract: We prove the explicit version of the Buzzard-Diamond-Jarvis conjecture formulated in [DDR16]. More precisely, we prove that it is equivalent to the original Buzzard-Diamond-Jarvis conjecture, which was proved for odd primes (under a mild Taylor-Wiles hypothesis) in earlier work of the third author and coauthors.1991 Mathematics Subject Classification. 11F80,11F41.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Moreover in the formula (24) for such v, we have J = J 1 = J 2 , w = w 1 = w 2 , β 1 ≡ β 2 ≡ 1 mod pO F,p and Nm F/Q (v) ≡ 1 mod p, so that r J,w 0 (T v f ) = 2r J,w 0 (f ). Therefore if r J,w 0 (f ) = 0 for some (J, w), then ρ f (Frob v ) has characteristic polynomial (X − 1) 2 for such v. By the Cebotarev Density Theorem (and class field theory) it follows that ρ f (g) has characteristic polynomial (X − 1) 2 for all g ∈ G K , where K is the strict ray 6 Alternatively, this can be proved by revisiting the construction in Theorem 6.1.1 and observing that if r J,w 0 = 0 for some (J, w), then the liftf is non-cuspidal. One then deduces that the Galois representation ρf is reducible, and hence so is ρ f (possibly after extending scalars in the case p = 2).…”
Section: Normalised Eigenformsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover in the formula (24) for such v, we have J = J 1 = J 2 , w = w 1 = w 2 , β 1 ≡ β 2 ≡ 1 mod pO F,p and Nm F/Q (v) ≡ 1 mod p, so that r J,w 0 (T v f ) = 2r J,w 0 (f ). Therefore if r J,w 0 (f ) = 0 for some (J, w), then ρ f (Frob v ) has characteristic polynomial (X − 1) 2 for such v. By the Cebotarev Density Theorem (and class field theory) it follows that ρ f (g) has characteristic polynomial (X − 1) 2 for all g ∈ G K , where K is the strict ray 6 Alternatively, this can be proved by revisiting the construction in Theorem 6.1.1 and observing that if r J,w 0 = 0 for some (J, w), then the liftf is non-cuspidal. One then deduces that the Galois representation ρf is reducible, and hence so is ρ f (possibly after extending scalars in the case p = 2).…”
Section: Normalised Eigenformsmentioning
confidence: 98%
“…Proof. 6 If v is trivial in the strict class group of conductor np, then it follows from the definitions that S v acts trivially on M k,l (U ; E). Moreover in the formula (24) for such v, we have J = J 1 = J 2 , w = w 1 = w 2 , β 1 ≡ β 2 ≡ 1 mod pO F,p and Nm F/Q (v) ≡ 1 mod p, so that r J,w 0 (T v f ) = 2r J,w 0 (f ).…”
Section: Normalised Eigenformsmentioning
confidence: 99%
“…At the time, we reported that a proof of Conjecture 7.2 under certain genericity hypotheses would be forthcoming in the Ph.D thesis of Mavrides [19]. In fact, Conjecture 7.2 has now been proved completely by Calegari, Emerton, Gee, and Mavrides in a preprint posted to the arXiv in August 2016 [5]. We remark that our restriction to the case where K is unramified over Q p is made essentially for simplicity.…”
Section: Introductionmentioning
confidence: 96%
“…We remark that our restriction to the case where K is unramified over Q p is made essentially for simplicity. The methods of this paper, and indeed of [5], are expected to apply to the general case where K/Q p is allowed to be ramified, but the resulting explicit description of the distinguished subspaces is likely to be much more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…A definition of W (ρ) was first given in [BDJ10] in the case that K/Q l is unramified, and various generalisations and alternative definitions have subsequently been proposed. As a result of the main theorems of [GLS15,CEGM], all of these definitions are equivalent; we refer the reader to the introductions to those papers for a discussion of the various definitions.…”
Section: 2mentioning
confidence: 99%